What Do Teachers Know and Do? Does It Matter? : Evidence from Primary Schools in Africa - Bold, Tessa; Filmer, Deon; Martin, Gayle; Molina, Ezequiel; Rockmore, Christophe; Stacy, Brian; Svensson, Jakob; Wane, Waly (World Bank, Washington, DC, 2017)
School enrollment has universally increased over the past 25 years in low-income countries. However, enrolling in school does not guarantee that children learn. A large share of children in low-income countries learn little, and they complete their primary education lacking even basic reading, writing, and arithmetic skills—the so-called "learning crisis." This paper uses data from nationally representative surveys from seven Sub-Saharan African countries, representing close to 40 percent of the region's total population, to investigate possible answers to this policy failure by quantifying teacher effort, knowledge, and skills. Averaging across countries, the paper finds that students receive two hours and fifty minutes of teaching per day—or just over half the scheduled time. In addition, large shares of teachers do not master the curricula of the students they are teaching; basic pedagogical knowledge is low; and the use of good teaching practices is rare. Exploiting within-student, within-teacher variation, the analysis finds significant and large positive effects of teacher content and pedagogical knowledge on student achievement. These findings point to an urgent need for improvements in education service delivery in Sub-Saharan Africa. They also provide a lens through which the growing experimental and quasi-experimental literature on education in low-income countries can be interpreted and understood, and point to important gaps in knowledge, with implications for future research and policy design.